Light, lenses and lasers - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 1997)
Examines the sources of natural, artificial, biological, and reflected light and the properties and uses of lenses and lasers
Installation guide : Macintosh, drag folder to hard drive, the double click on the program icon ; Windows, run'INSTALLE.EXE' from the cd-rom, then double click the program icon
Title from disc label
Keywords: Optical instruments -- Juvenile literature; Light sources -- Juvenile literature; Lenses -- Juvenile literature; Lasers -- Juvenile literature; Light; Lenses; Lasers; Optics